Charged particle multiplicity distributions in Z0 hadronic decays - Abreu, P; Adam, W; Adami, F; Adye, T; Alexeev, G; Allen, P; Almehed, S; Alted, F; Alvsvaag, S; Amaldi, U; Anassontzis, E; Apel, W; et al. (1991)
This paper presents an analysis of the multiplicity distributions of charged particles produced in Z0 hadronic decays in the DELPHI detector. It is based on a sample of 25364 events. The average multiplicity is <nch>=20.71±0.04(stat)±0.77(syst) and the dispersion D=6.28±0.03(stat)±0.43(syst). The data are compared with the results at lower energies and with the predictions of phenomenological models. The Lund parton shower model describes the data reasonably well. The multiplicity distributions show approximate KNO-scaling. They also show positive forward-backward correlations that are strongest in the central region of rapidity and for particles of opposite charge. © 1991 Springer-Verlag.</nch>